Endobronchial cryptococcosis with bronchial stenosis in a patient with severe asthma treated with inhaled corticosteroids: A case report - Jun Sasaki; Takashi Kinoshita; Misa Sudou; Takayuki Horii; Reiko Takaki; Masahiro Mitsuoka; Masaki Tominaga; Tomotaka Kawayama; Tomoaki Hoshino (Respirology Case Reports, 2023)
Abstract Cryptococcosis typically manifests as pulmonary lesions, with endobronchial lesions occurring rarely. Inhaled corticosteroids (ICS) may be a risk factor for cryptococcosis of the larynx but not of the bronchi. Here, we report a case involving a 73‐year‐old Japanese man who developed endobronchial cryptococcosis during ICS treatment for asthma. Chest computed tomography showed right mainstem bronchial stenosis and asthma control worsening when he received adequate asthma treatments. Bronchoscopy revealed multiple elevated lesions with white slough from the trachea to the right mainstem bronchus and the right mainstem bronchus lumen entrance narrowing. Bronchial lavage culture revealed Cryptococcus neoformans. Combination treatment with the antifungal agent, mepolizumab, and bronchodilation surgery successfully controlled cryptococcosis and asthma. Attention should be paid to central airway lesions during ICS treatment for uncontrolled asthma.